QUALITY CONTROL OF NATURAL GAS – A NEW SOLUTION - I. J. Darvay; M. O. Karpash; I. V. Rybicki (Литьë и металлургия)
Scientific support of the new method of determination of the natural gas combustion heat is considered. The developed method is realized in the experimental installation which passed industrial testing.